Relationship among Amlapitta and Lifestyle and its Treatment through Lifestyle Management - Pandey, Naranath; Pokhrel, Hari Prasad; Pokhrel, Sanjaya; Dhakal, Mati Prasad (Madhyabindu Journal, 2024)
Among the various diseases that appear due to deviations in lifestyle, one of the diseases related to the stomach and oesophagus is also hyperacidity. The presented study is the relationship between amlapitta and lifestyle and its treatment through lifestyle management. There are mainly three problems in the study of lifestyle management for the treatment of amlapitta- What are the relationships between amlapitta and lifestyle? What aspects of lifestyle can cure amlapitta? And how can it be established that the treatment of amlapitta is through lifestyle management? There are the following three objectives to solve this problem- to analyze the relationship between amlapitta and lifestyle, to present alternative treatment methods for amlapitta by directly practising aspects of lifestyle management, and to establish recognition based on the facts that amlapitta can be treated by lifestyle management. In the present study, there are 120 people in the treatment group and 40 people in the control group, a total of 160 people related to amlapitta. Interview, rating scale and direct practice method are followed. Data is presented using tables, bar diagrams and pie charts. APA 7 method and SPSS application are used. The study is limited only to the urban area of Kawasoti and Madhyabindu municipality and the hilly area of Hupsekot village of Nawalpur district. Based on the research that focused on the 11 problems included in its study, it was found that amlapitta was cured by lifestyle management in three groups, while no improvement was found in the control group.